Cost-effectiveness of total knee arthroplasty, unicompartmental knee arthroplasty, and high tibial osteotomy for medial compartment knee osteoarthritis in young patients: a Canadian public payer perspective - Pakpoom Ruangsomboon; Onlak Ruangsomboon; Davis Tam; Bheeshma Ravi; Seper Ekhtiari; Daniel Pincus; Sebastian Tomescu (Journal of Orthopaedic Surgery and Research)
Abstract Background In medial compartment osteoarthritis (OA) of the knee in young patients who fail conservative treatment, clinical equipoise exists between three surgical strategies: (1) total knee arthroplasty (TKA), (2) unicompartmental knee arthroplasty (UKA), and (3) medial opening wedge high tibial osteotomy (HTO). This study evaluated the cost-effectiveness of three surgical strategies, using a probabilistic Markov model from the Ontario public payer perspective in Canada. Methods A probabilistic Markov model was developed to perform a cost-utility analysis comparing TKA, UKA, and HTO. The base case simulated a 45-year-old Canadian cohort with unilateral medial knee OA over a lifetime horizon. Outcomes included quality-adjusted life months (QALMs), discounted lifetime costs (1.5% annually), incremental cost-effectiveness ratios (ICERs), and net monetary benefit (NMB), reported in 2023 Canadian dollars (CAD, $). A willingness to pay (WTP) threshold of $4,166.67/QALM was applied. Model uncertainty was assessed via 3,000 iterations of probabilistic sensitivity analysis. Scenario analyses using sex-specific mortality rates were also conducted. Results Mean costs were $9,157 (TKA), $9,238 (HTO), and $9,419 (UKA). UKA produced the highest QALMs (290.53), followed by TKA (277.02) and HTO (270.88). HTO was absolutely dominated, as it was both more costly and less effective than TKA. Among undominated strategies, UKA yielded an ICER of $19.46/QALM compared to TKA. UKA also had the highest NMB ($1,201,112), outperforming TKA ($1,145,110) and HTO ($1,119,411). UKA was the most cost-effective option in 55.27% of probabilistic simulations, followed by TKA (23.83%) and HTO (20.90%). Scenario analyses with sex-specific mortality showed similar trends. Conclusions UKA is the most cost-effective surgical strategy from a public payer perspective for young patients with medial knee OA. At a WTP of $4,166.67/QALM, UKA balances long-term durability and economic value better than TKA or HTO. Level of evidence Level III, Model-based economic evaluation.